Frederik Kaiser (1808-1872), een gekweld man met een missie - Zuidervaart, Huib (Studium, 2011)
Frederik Kaiser (1808-1872), a tormented man with a missionThe Leiden astronomer Kaiser has been instrumental for the rise of Dutch astronomy in the late nineteenth-century. His career was impressive. In 1826, without any formal university education, he began at the Leiden Astronomical Observatory as an ordinary observer. Through his work in astronomy he obtained an honorary doctorate, which enabled him in 1838 to become director of the observatory. In 1844 he was appointed full professor and in the academic year 1857/1858 he even became Rector Magnificus of Leiden University. In 1860 he even saw the fulfillmentof his life-long dream: the opening of a brand new astronomical observatory. However, in spite of these obvious professional successes, Kaiser's personal life was full of melancholy. This paper investigates Kaiser's personality, using correspondence with his family, as well as testimonies written down by his students and other contemporaries. Among others, we demonstrate the way in which Kaiser used his personal network, as well as his fierce continuous – and often publicly expressed – complaining, as a successful strategy in establishing his new astronomical observatory.